Research on the Percolation Mechanism of Perturbation Under Simultaneous Fracturing in Shale Reservoirs - He, Jie; Niu, Xiaobing; Meng, Qingchun; Guo, Fajun; Wang, Hongmei; Liu, Yicang; Wang, Lianguo; Kang, Yongmei; Hu, Kelai; Zhu, Yushuang (Frontiers in Energy Research, 2021)
Compared with conventional reservoirs, shale gas reservoirs usually have no natural productivity or lower productivity, and the production decline is faster in the later stage. The production effect of shale gas can be effectively improved by designing well pattern reasonably or fracturing in the later stage. Therefore, it is critical for shale gas reservoir to study on how to design well pattern and set reasonable fracturing parameters reasonably in order to make it effectively developed. Based on data of block-A shale gas field of Zhejiang region, considering the contribution of rock compression to the production of fluid, the productivity formula of the shale gas horizontal well development mode at different seepage stages is deduced. Data of A shale gas field is verified by orthogonal experiment, including gas reservoir parameters and engineering parameters. The results show that: the order of gas reservoir parameters that affect the development of shale gas is as follows: Langmuir pressure, inter-porosity flow parameter, diffusion coefficient, Langmuir volume; the order of engineering parameters that affect the development of shale gas is as follows: the number of fractures, the horizontal section length, production pressure, fractures length, row spacing and well spacing. The research results have been applied to Zhejiang oilfield. After the preliminary implementation in the field, the decline rate of shale gas has slowed down by 26.08%. The research results have important reference significance for the efficient development of similar gas reservoirs.